Association of Accelerometer-Measured Sedentary Behavior Patterns With Nonalcoholic Fatty Liver Disease Among Older Adults: The MIND-China Study. (14th March 2023) - Han, Qi; Han, Xiaolei; Wang, Xiaojie; Wang, Chaoqun; Mao, Ming; Tang, Shi; Cong, Lin; Hou, Tingting; Liu, Cuicui; Wang, Yongxiang; Du, Yifeng; Qiu, Chengxuan
Abstract : INTRODUCTION: The relationships between sedentary behavior patterns and nonalcoholic fatty liver disease (NAFLD) in older adults are not well investigated. METHODS: This population-based study included 1, 899 rural-dwelling adults (aged 60 years or older). We assessed sedentary parameters with ActiGraph and defined NAFLD using ultrasonography. RESULTS: Long total and prolonged sedentary time were associated with increased likelihoods of NAFLD, whereas engaging more breaks per sedentary hour and reallocating sedentary time to light-intensity physical activity were associated with reduced likelihoods of NAFLD (Plinear <0.05). DISCUSSION: Shorter sedentary time, engaging more frequent breaks in sedentary behavior, and replacing sedentary time with physical activity are associated with reduced likelihoods of NAFLD in older adults.